Microscopic characterization of residual particles from filtered drinking water and determination of statistical indicators regarding identified deposits - Crișan, Horea-George; Crișan, Oana-Adriana; Bîrleanu, Corina; Pustan, Marius; Șerdean, Florina (Frontiers in Earth Science, 2023)
The study shows the findings of a microscopic examination of samples of filtered water obtained using five different types of filters. Atomic force microscopy was used to carry out the analysis, and particular mathematical models were used to statistically evaluate the findings. The paper explains the methodology used, including details on the laboratory setup, the steps finished, and the tools used to accomplish the suggested goals. With an emphasis on the three dimensions of the particles—height, diameter, and arithmetic roughness—the findings from the microscopic analysis of the particle deposits on the filtered water samples are given and tabular indexed. As a result, it was feasible to use a computational mathematical model to identify the statistical indicators of the values recorded in the samples that underwent microscopical analysis. Following the application of the mathematical model, the findings were centralized, and their correlation was analyzed using graphical representations. The results led to the concrete identification of the impurity degree of drinking water filtered by consumer means.